2018
DOI: 10.1002/aic.16420
|View full text |Cite
|
Sign up to set email alerts
|

Designing amino‐based ionic liquids for improved carbon capture: One amine binds two CO2

Abstract: Generally, amine group captures CO 2 according to 2:1 or 1:1 stoichiometry. Here, we report a kind of improved carbon capture using amino-functionalized ionic liquids (ILs) through 1:2 stoichiometry. A serial of amino-functionalized ILs various with basicity and steric hindrance of anion were designed, prepared, and applied in CO 2 capture. Through a combination of absorption experiment, quantum chemical calculation, spectroscopic investigation and calorimetric method, the results indicated that one amine grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…39 d) Proposed absorption mechanism for an IL with an aspartate dianion. 40 In all cases, the corresponding cations are omitted for clarity.…”
Section: New Co2 Chemisorption Pathways In Solution and The Solid Statementioning
confidence: 99%
“…39 d) Proposed absorption mechanism for an IL with an aspartate dianion. 40 In all cases, the corresponding cations are omitted for clarity.…”
Section: New Co2 Chemisorption Pathways In Solution and The Solid Statementioning
confidence: 99%
“…Ionic liquids with amine groups generally absorb CO 2 in a 2:1 or 1:1 molar ratio by forming a carbamate. Luo et al 91 have prepared ionic liquids with amino functionalised anions which can capture CO 2 in almost a 1:2 ratio. (Figure 18).…”
Section: Co 2 Capture and Valorisationmentioning
confidence: 99%
“…Other authors have reported larger absorption capacity up to 1:2 M ratio. In a first work (Luo et al 2019 ), a set AAILs with different basicity and steric hindrance was tested. It was found that the di-anion of a doubly deprotonated AA such as Asp showed a very high absorption capacity of 1.96 mol/mol IL at 30 °C and 1 atm.…”
Section: Chaail As Candidates For Co 2 Absorptionmentioning
confidence: 99%